Physical and chemical properties of the sediments of the banks of Shatt al-Basrah Canal - Salem Shaaban Jaber , Maryam; Nazir Al-Khayat , Prof. Dr. Namir (Basra studies journal, 2023)
Shatt al-Basra canal was dug in the southern part of the sedimentary plain in the areas of swamp lands as part of the general estuary project to Khor al-Zubayr. It extends about 38 km from north to south. Six stations along the canal have been selected from sites representing bank sediments runoffs. Directly or indirectly, some geographical factors played a great role in the stability of the sediments of the banks, including the geological factor, the slope of the surface and the climatic characteristics in terms of drought, humidification, dry winds, evaporation, sediment separations and their type. The hydrological situation, drainage and tidal phenomena also had an impact on the instability of the banks sediments. The human factor also had a role through the construction of bridges, roads and engineering projects across the canal, which affected the cross-sectional area as well as the practice of fishing and buffalo grazing. It turned out that the site of Shatt al-Basra regulator, by preventing tidal water from penetrating along the canal, created two different environments in their physical, chemical, engineering and morphological characteristics, and was reflected in showing the contrast between the first, second, third and fourth stations with the fifth and sixth stations, which are located to the south of the regulato, on the stability of the sediments of the banks, and it was found that the slopes of the banks of Shatt al-Basra canal were within the medium-height slope according to the geometric dimensions of the banks.